Trains, literature, and culture reading/writing the rails - Spalcing, Steven D.; Fraser, Benjamin (Lexington Books, 2012)
"Trains, literature and culture is the first work to thoroughly explore the railroad's connections with a full range of cultural discourses--including literature, visual art, music, graffiti, and television but also advertising, architecture, cell phones, and more ..."--Provided by publisher.